1998
DOI: 10.1177/089826439801000302
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Factors Associated with Perceived Quality of Life

Abstract: Demographic and social network factors associations with perceived quality of life (PQOL) were examined in a sample of rural Hispanic and non-Hispanic White (NHW) elderly. A 20-item PQOL scale measured participants' satisfaction with multiple facets of their lives. Age, gender, marital status, and living alone were not associated with this outcome. Hispanic persons with higher incomes had consistently higher ratings of quality of life compared to NHWs. More education was associated with a higher PQOL ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 30 publications
3
45
0
3
Order By: Relevance
“…This could be related with findings indicating that life satisfaction in women is positively explained by perceived social support [30]. Perceived availability of emotional support, reassurance, instrumental assistance, and companionship provided by social network partners such as a family have consistently been reported to be related to better life satisfaction [31,32]. In general, women are more sensitive to their social networks than are men [33].…”
Section: Discussionmentioning
confidence: 66%
“…This could be related with findings indicating that life satisfaction in women is positively explained by perceived social support [30]. Perceived availability of emotional support, reassurance, instrumental assistance, and companionship provided by social network partners such as a family have consistently been reported to be related to better life satisfaction [31,32]. In general, women are more sensitive to their social networks than are men [33].…”
Section: Discussionmentioning
confidence: 66%
“…Meanwhile, the negative association between anxiety symptoms and QOL in the social relationship domain was more significant in girls than in boys. Research found that perceived availability of emotional support, reassurance, instrumental assistance, and companionship provided by social networks are related to better life satisfaction [21]. In general, women are more sensitive to their social networks than men [22].…”
Section: Discussionmentioning
confidence: 98%
“…Heller and Mansbach (1984) find that the size of social networks is a significant determinant of life satisfaction and psychological well-being among elderly women. Baxter and et al (1998) find that the size of old people's social networks is associated with their perceptions of life quality. Vandervoort (1999) reports that network size, namely the total number of children, relatives and friends of the respondent, is strongly related to depression and anxiety.…”
Section: Literature Reviewmentioning
confidence: 97%